Hospitalisation of late preterm infants due to lower respiratory tract infections in Lithuania, Latvia, and Estonia: incidence, disease severity, and risk factors - Drazdienė, Nijolė; Tamelienė, Rasa; Kviluna, Daiga; Saik, Pille; Saik, Ervin; Zaikauskienė, Jolanta (Acta medica Lituanica, 2018)
Background. By two years of age, almost all children experience at least one episode of respiratory syncytial virus (RSV) infection, the most common viral cause of hospitalisation due to lower respiratory tract infection (LRTI). We present data on LRTI hospitalisations (with a special focus on RSV), the course of illness, and LRTI hospitalisation risk factors in Lithuania, Latvia, and Estonia. Materials and methods. The analysed data were part of a large multinational study conducted in 23 countries (PONI). LRTI-related hospitalisations were observed during one RSV season for late premature infants (born between 33 weeks and 0 days and 35 weeks and 6 days of gestation) ≤6 months of age, who did not receive RSV prophylaxis. The potential risk factors and demographics were recorded at study enrolment and at the end of the RSV season. The primary endpoint was hospitalisation due to RSV LRTI; the secondary endpoints included severity, the course and the outcome of LRTI hospitalisations. Results. Out of the 291 infants enrolled in three Baltic states, 19 were hospitalised due to LRTI (6.5%). RSV testing was performed for 14 hospitalised infants; five infants had a positive test for RSV (1.7%). The majority of the hospitalised infants (94.7%) had mild or moderate respiratory illness. Male sex, O2 dependency after birth, younger maternal age, and furred pets at home were significantly associated with an increased risk for LRTI hospitalisation. Conclusions. During one RSV season, the incidence of LRTI hospitalisations among late preterm infants was 6.5% and the incidence of RSV LRTI hospitalisations was 1.7%.